Studi Kausal Budaya Organisasi, Komitmen Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan - Nihayatul Fadlilah; Mukson; Slamet Bambang Riono; Dwi Harini; Andi Yulianto (Program Studi Manajemen Universitas Muhadi Setiabudi, 2019)
This research aims to know and analyse, causal studies of organizational culture, organizational commitment and work motivation towards employee performance. Using quantitative approach method with survey. Data was taken through the technique of sample random sampling (simple randomized technique) of the population number of 3500 employees and sampled 10% of the population is 98 employees. Data collection using questionnaires while data analysis is done using multiple regression analysis. And data processing using SPSS. The results show that there is no cultural influence on the organization's performance, there is a influence of organisational commitment to employee performance and there is no influence of work motivation to employee performance. Simultaneously means the organizational culture, and the motivation of work has no effect while the organizational commitment significantly affects the employee's performance